Structuralization of magnetic nanoparticles in 5CB liquid crystals - Gdovinová, Veronika; Appel, Ingo; Behrens, Silke (Soft matter, 2017)
This work is devoted to the study of highly stable composite systems of the liquid crystal 4-n-pentyl-4′-cyanobiphenyl (5CB) doped with CoFe2O4 magnetic nanoparticles. Ferronematic samples were prepared with two different weight concentrations: sample A 0.085 wt% and sample B 0.062 wt%. The interaction of CoFe2O4 nanoparticles with the liquid crystal was investigated by small-angle X-ray-scattering and magnetization measurements. The obtained results reveal aggregates formed by magnetic nanoparticles that are oriented in the nematic phase. Moreover, the prepared samples show unexpected behaviour of a sudden change in magnetization, which is unusual for such ferronematics.